Dynamic Braking Modes of Linear Induction Drive - Rinkevičienė, R.; Lisauskas, S. (Elektronika ir Elektrotechnika, 2005)
The article presents investigation into dynamic modes of braking of linear induction drives when motors windings are supplied by direct current. Dynamic models of braking are developed for three different connection types of windings. During braking linear motor windings are supplied by asymmetrical voltage. Models of linear electric drives are developed for direct, inverse and zero components. Dependences of braking duration on winding connection type and supplied voltage is investigated. Dependences of linear motor developed force, inductor current and secondary element current against time are analyzed at different windings connection type. Discussed dynamic processes of braking linear motors by direct current allows to choose a scheme of linear induction motors connection and to form required dynamic characteristics of braking. Ill. 7, bibl. 12 (in Lithuanian, summaries in Lithuanian, English and Russian).